2021
DOI: 10.3390/diagnostics11061100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quantitative Ga-68 PSMA PET/CT Repeatability of Recurrent Prostate Cancer Lesions Using Both OSEM and Bayesian Penalized Likelihood Reconstruction Algorithms

Abstract: Rationale: To formally determine the repeatability of Ga-68 PSMA lesion uptake in both relapsing and metastatic tumor. In addition, it was hypothesized that the BPL algorithm Q. Clear has the ability to lower SUV signal variability in the small lesions typically encountered in Ga-68 PSMA PET imaging of prostate cancer. Methods: Patients with biochemical recurrence of prostate cancer were prospectively enrolled in this single center pilot test-retest study and underwent two Ga-68 PSMA PET/CT scans within 7.9 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…BPL reconstruction (also known as Q.Clear in GE Healthcare Imaging) is a relatively newer reconstruction method with the capacity to improve contrast over OSEM, by applying a noise penalty to individual voxels during reconstruction [ 8 10 ]. From a clinical point-of-view, BPL reconstruction improves the signal-to-noise ratio (SNR) and have been reported to be useful for better localization of the tumour as reported in case reports [ 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BPL reconstruction (also known as Q.Clear in GE Healthcare Imaging) is a relatively newer reconstruction method with the capacity to improve contrast over OSEM, by applying a noise penalty to individual voxels during reconstruction [ 8 10 ]. From a clinical point-of-view, BPL reconstruction improves the signal-to-noise ratio (SNR) and have been reported to be useful for better localization of the tumour as reported in case reports [ 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Demographics, clinicopathologic, and treatment information were collected. The images were reconstructed once as being done routinely using GE-VPFXS algorithm (OSEM incorporating time-of-flight and resolution recovery using 2 iterations and 24 subsets, matrix size:192 × 192, Gaussian filter: 6.4 mm) and then by BPL algorithm (Q.Clear with a Beta value of 600 and same matrix size of 192 × 192) [ 8 ]. Subsequently, the images were processed by a nuclear medicine doctor experienced in [ 68 Ga]Ga-PSMA-11 image processing using MIM version 7.1 (MIM software, Beachwood, OH, USA), and the standardised uptake value (SUV)max, SUVmean and Molecular Tumour Volume (MTV-PSMA) were calculated in each set of reconstructed images separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of BPL reconstruction algorithms allows for more iterations to be performed relative to OSEM-PSF while maintaining a similar noise level; this can improve image quality and enhance quantitative accuracy. BPL reconstruction algorithms have existed since 1987 but their clinical use has thus far been limited [14,15], with isotope specific characterization of BPL reconstruction algorithm performance being performed with F-18 and Ga-68 [16,17]. To the knowledge of the authors, no similar characterization studies have been performed for Cu-64.…”
Section: Introductionmentioning
confidence: 99%
“…Serial scanning allows the measurement of functional changes over time during therapeutic interventions. In this Special Issue, Roef and colleagues determined the repeatability of 68 Ga-PSMA lesion uptake in both relapsing and metastatic tumors and showed that a minimum response of 50% seems appropriate in this clinical situation [ 10 ], which is higher than 30% recommended by the PET Response Criteria in Solid Tumors [ 11 ]. In this Special Issue, three articles investigated the prognostic value of 18 F-FDG PET imaging.…”
mentioning
confidence: 99%